CRETACEOUS ROCKS OF MISOOL ARCHIPELAGO, INDONESIA - Fauzie Hasibuan; E Rusmana (Jurnal Geologi dan Sumberdaya Mineral, 2007)
Cretaceous  rocks of  Misool  Archipelago   are exposed  mostly on the southern  part of the main  island  of Misool and its adjacent  islets.  The rocks belong to the upper  part of Lelinta  Formation,  Facet Limestone  Group  (Waaf  Formation  and Gamta  Formation),  Fafanlap  Formation  (Yabatano  Member)   and  lower  part of Daram Formation.  The age of the rocks ranges from Aptian  to Maastrichtian  based on their fossil content. The lithology of each formation is redescribed herein.The results show that almost  the whole  formations contain macrofossils such as molluscs and microfossils (foraminifera). The  Gamta Formation  (the oldest)  is  Late  Berriasian to Middle   Cenomanian   in age  based  on  the occurrences  of  Ptilorhynchia  sp., Proclydonophora  sp., Rotularia sp.,  Buchia sp .. ammonite  gen.  et sp. indet, coral indet., and  trace fossils.  Early  Cretaceous  is also indicated  by the presence of Hibolithes  gamtaensls,  H.  miosensis,  Duvalia  spp.,  and Belemnopsis jonkeri. Waaf Formation  (Middle  Cenomanian   to Early Campanian)  contains  rich globigerinid  and other microfossils,  trace fossils, large Inoceramus  up to 70 cm in length with oysters attached to it, and Prochlydonophora   sp. But, this bivalve  is very difficult  to sample. The upper part of the Waaf Formation oontains  abundant  microfossils,  probably indicating  a bathyal   environmenl Fafanlap  Formation and its Yabatano Member contain  micro and macrofossils such as Inoceramus  misoliensis, I. (Cordiceramus}  paraheberti, I.  (C.) cf. pseudoregularis, t. (Selenoceramus)  sufflatus and t.haani,  Durania wanneri, and burrows indet. Micraster and Hemiaster were difficult  to sample,  and so were minor  coral and bryozoan.   lnoceramus spp. which are found  in the lower  part of Fafanlap  Formation  indicate  a Middle  Campanian age. The microfossils  range up to Maastrichtian.  It can be concluded that the age of Fafanlap  Formation  is Late Santonian up to late  Maastrichtian   and  at least Late  Maastrichtian  for the Yabatano  Member.   Based  on the assemblage  of microfossils  reported  by previous workers, the age of the Daram  Formation  in the tower part  can be assumed   as Late Maastrichtian.Biostratigraphic correlation  of Lower Cretaceous in Indonesian  Archipelago  based on microfossils  promising for the islands of Rote,  Timor,  Seram,   Buru, Buton,  the eastern,  central  and south  arms of Sulawesi,  Halmahera,   New Guinea   and perhaps Obi and eastern Kalimantan.  In the upper Cretaceous,  inooeramid  bivalves are more common  and are closely related to those of New Guinea and Madagascar.Cretaceous of the Misool  Archiprelago  is the most difficult part to correlate  within  Indonesia  based on microfossils at present, but is promising   in the future study.   The microfauna  of Misool  is closely  related  to that of the Emscher Marl of Westfalen  In Europe. Theforaminifera  also resemble those of theSeweer   Beds in the European  Alps.   The Easy Cretaceous of the upper part of the lochambel  Beds of Spiti, India  with  the Neocosmoceras-Distoloceras   Assemblage  is probably correlatable  with the upper part  of the lelinta  Formation  of Misool. In Misool, however the latter   is dominated bybelemnites even though similar  in rock facies (chert-bearing   beds).  The inoceramid  species trom Misool,  e.g. lnoceramuscf.  bererensis,  I.  (Cordiceramus)   paraheberti and  I, (C.}  cf. pseudoregularis  are  closely similar to those found inMadagascar,  some perhaps beingcoospecific,   and in both area indicating  a Middle  Campanian  age.Keywords: Misool Archipelago,Cretaceous, Lelinta Formation, Gamta Formation,Waaf Formation, Fafanlap Formation, D aram Formation, inoceramids, belemniles, foraminifera